Unusual Bleeding Due to Riociguat Use in a Patient With Chronic Thromboembolic Pulmonary Hypertension - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2016)
Riociguat is a new drug prescribed to patients with pulmonary hypertension that reduces the pressure in pulmonary artery by vasodilation. This drug like many other drugs has several side effects, some of which can be serious such as bleeding. Riociguat causes vaginal bleeding by increasing endometrial thickness and blood flow to the endometrium, therefore, should be used with care especially for patients who have history of dysfunctional uterine bleeding. In this case report, we present a 27-year-old female patient with chronic thromboembolic pulmonary hypertension and dysfunctional uterine bleeding presented with severe vaginal bleeding under riociguat treatment.
Keywords: riociguat; pulmonary hypertension; bleeding; anemia